2020
DOI: 10.3390/jcm9061967
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the Surface Electromyographic Assessment of Pelvic Floor Muscles in Women with Stress Urinary Incontinence

Abstract: Background: The use of surface electromyography (sEMG) measurements to evaluate the bioelectrical activity of the pelvic floor muscle (PFM) during therapeutic intervention is now well established. This study investigates the diagnostic possibilities of sEMG in women with stress urinary incontinence (SUI). The aim of this study was to carry out objective assessments of the bioelectrical activity of the PFM in women after menopause and determine the prognostic value of sEMG for assessing the PFM in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Observation of changes in EMG signal would be beneficial, especially in view of the results of studies by some authors who found lower electromyographic activity in women with UI compared with healthy women. 19 Thus, it appears that the existing dysfunction which is UI could be related to dysfunction also of the passive component of muscle tone, such as soft tissue stiffness and elasticity, as in the study by Barrasi et al 17 In this study, neuromuscular manual therapy and vibration were used to treat UI symptoms, flexibility, stiffness, and myofascial tone in 60 women aged 50-70 years. The intervention protocol included eight sessions of vibration therapy and manual techniques that resulted in significant changes in all parameters of flexibility and stiffness of the myofascial structures studied and treated.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Observation of changes in EMG signal would be beneficial, especially in view of the results of studies by some authors who found lower electromyographic activity in women with UI compared with healthy women. 19 Thus, it appears that the existing dysfunction which is UI could be related to dysfunction also of the passive component of muscle tone, such as soft tissue stiffness and elasticity, as in the study by Barrasi et al 17 In this study, neuromuscular manual therapy and vibration were used to treat UI symptoms, flexibility, stiffness, and myofascial tone in 60 women aged 50-70 years. The intervention protocol included eight sessions of vibration therapy and manual techniques that resulted in significant changes in all parameters of flexibility and stiffness of the myofascial structures studied and treated.…”
Section: Discussionmentioning
confidence: 76%
“…Our results, as well as previous studies, indicate that manual therapy has no significant effect on the active component of muscle tone, that is, electromyographic activity. Observation of changes in EMG signal would be beneficial, especially in view of the results of studies by some authors who found lower electromyographic activity in women with UI compared with healthy women 19 . Thus, it appears that the existing dysfunction which is UI could be related to dysfunction also of the passive component of muscle tone, such as soft tissue stiffness and elasticity, as in the study by Barrasi et al 17 In this study, neuromuscular manual therapy and vibration were used to treat UI symptoms, flexibility, stiffness, and myofascial tone in 60 women aged 50–70 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen PSUI patients and fifteen postpartum asymptomatic women with matching personal information participated in the clinical trial. They conducted Glazer protocol [ 25 , 26 ] and we applied MET to comparing the evaluation parameters. Results showed that the PSUI patients had weaker PFM reactivity and strength than those of the health control group, and the type-I and type-II muscle dysfunctional regions are mostly located in the iliococcygeus, pubococcygeus, and urethral sphincter regions.…”
Section: Introductionmentioning
confidence: 99%
“…The weakening of the particular components of the pelvis and PF may lead to the occurrence of pathological symptoms associated with the deterioration of their function. Therefore, a proper diagnosis and therapeutic management play a crucial role in preventing and moderating the discussed dysfunctions, especially during menopause [4,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%